This Is Why We Can't Have Nice Things: Mapping the Relationship between Online Trolling and Mainstream Culture - Phillips (MIT Press, 2015)
Monograph
fulltext
Keywords: Computing and Processing; General Topics for Engineers; Communication, Networking and Broadcast Technologies